IOT-based Soil Moisture Monitoring and Water Pump Control System for Ornamental Plants: Sistem Monitoring Kelembapan Tanah Dan Kendali Pompa Air Tanaman Hias Berbasis Iot - Attalarik Zidan; Yunita Rahma; Sufiatul Maryana (Program Studi Ilmu Komputer, Universitas Pakuan, 2025)
Ornamental plants cultivation is a type of plant cultivation that is growing rapidly and also has great potential in Indonesia. In Bogor Regency itself, many farmers started developing this ornamental plant after the Pandemic Era. The unique tropical pattern has become a surge in market demand, one of which is the Syngonium type. The challenges for farmers in cultivating ornamental plants come from the environment itself, the country's tropical climate causes Indonesia to have high rainfall and unpredictable heat. There are several types of plants whose growth process is very sensitive to the level of soil acidity. One solution to dealing with this problem factor is to apply intensification. This research aims to create a tool that is a monitoring and control system for water pumps to provide direct information about soil moisture as well as regular irrigation. The system was created using a capacitive soil sensor as input data for 3 soil conditions, namely Dry, Moist and Wet, then sent by the NodeMCU into the database to be displayed via the website and application, all of which are connected to the Arduino cloud, and received by a water pump for periodic irrigation. The result of this research is a prototype system for monitoring soil moisture and controlling water pumps for ornamental plants based on IoT which is expected to help farmers produce good planting media as well as good irrigation in the plant care phase.